Prevalence of Anti-Red Cell Antibodies in Repeatedly Transfused Patients (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: The development of anti-RBC antibodies (alloantibodies and/or autoantibodies) can significantly complicate transfusion therapy, particularly in patients needed repeated transfusion.Objectives: To find out the prevalence of alloantibodies and autoantibodies in repeatedly transfused patients so that serious hazards due to immune reaction may be avoided.Materials and Methods: This descriptive cross-sectional study was carried out in Department of Immunology, BIRDEM and Armed Forces Institute of Pathology (AFIP) during the period of July 2015 to June 2016. Total 370 patients who had received at least five units of transfusions were enrolled in this study but known patients of auto immune haemolytic anaemia, patients in whom antibody was previously detected and pregnant women were excluded from the study. Blood grouping and Direct Anti-globulin Test (DAT) were performed with cell suspension using a poly-specific Coombs reagent. In cases of a positive DAT, further investigation using specific monoclonal reagents to detect IgG or a complement (C3d) was carried out. Serum was used to detect red cell alloantibodies using standard blood bank methods. Antibody identification was performed in antibody screening positive samples using red cell Identicells.Results: Maximum 132 (35.7%) patients were in the age group 1-10 years. The male-female ratio was 1.2:1. Among 370 total patients 290 were HHA and 80 were non-HHA. Antibody was detected in only 17(4.59%) patients. Among the Hereditary Haemolytic Anaemia (HHA) patients it was 11 (3.79%) but among the non-HHA patients it was 6(7.5%). Out of 8 auto-antibodies, 5 were anti IgG followed by 3 were anti C3d. Out of 14 alloantibodies, 4(28.6%) were anti E, 3(21.4%) were anti K and in 3(21.4%) cases specificity of alloantibody was not detected.Conclusion: Prevalence of anti-RBC antibodies was not so uncommon in multiple transfused patients.Journal of Armed Forces Medical College Bangladesh Vol.14(1) 2018: 73-77